The current state of endoscopic disc surgery: review of controlled studies comparing full-endoscopic procedures for disc herniations to standard procedures - Birkenmaier, Christof; Komp, Martin; Leu, Hansjörg F.; Wegener, Bernd; Ruetten, Sebastian (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Background: Endoscopic spinal surgery is increasingly popular because it minimizes access trauma and hastens recovery from the intervention. Objective: To assess the clinical outcomes and complication rates of full-endoscopic disc surgery compared to the microsurgical standard procedures. Methods: A PubMed and Embase search was performed, considering entries up to January 2013. Only 5 controlled trials of 504 articles could finally be considered for evaluation. Results: Overall, the endoscopic techniques had shorter operating times, less blood loss, less operative site pain, and faster postoperative rehabilitation / shorter hospital stay / faster return to work than the microsurgical techniques. All 5 studies had fewer complications with the endoscopic technique. Conclusions: The studies show that full-endoscopic disc surgery can achieve the same clinical results in symptomatic cervical and lumbar disc herniations as the microsurgical standard techniques.